Sustaining Growth in Tourism Sector: Opportunities and Challenges - Mihir K. Mahapatra (Centre For Tourism Planning and Development, 2012)
The paper has broadly made an attempt to examine the growth and challenges faced by the tourism sector in Goa, a destination in India; during the last one decade.Of late, the number of tourists visiting the state is more than twice the population of the state. Empirical evidence also reveals an improvement in the growth of tourists' arrival but with wide fluctuation over the years. However, there are emerging issues of concern including the saturation of the carrying capacity of the state and the scope to sustain the growth momentum in the long run. Given the low geographical area and stiff competition among the destination managers to woo quality tourists, the state needs to be fully aware of their expectations and accordingly design the tourism policy.